2010
DOI: 10.1371/journal.pone.0012406
|View full text |Cite
|
Sign up to set email alerts
|

Specific Responses of Salmonella enterica to Tomato Varieties and Fruit Ripeness Identified by In Vivo Expression Technology

Abstract: BackgroundRecent outbreaks of vegetable-associated gastroenteritis suggest that enteric pathogens colonize, multiply and persist in plants for extended periods of time, eventually infecting people. Genetic and physiological pathways, by which enterics colonize plants, are still poorly understood.Methodology/Principal FindingsTo better understand interactions between Salmonella enterica sv. Typhimurium and tomatoes, a gfp-tagged Salmonella promoter library was screened inside red ripe fruits. Fifty-one unique c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
105
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 50 publications
7
105
2
1
Order By: Relevance
“…The main effects of the tomato cultivar (F ¼ 0.62, P ¼ 0.432) and Salmonella strain (F ¼ 0.60, P ¼ 0.4386) were not significant, while the main effects of the harvest time (F ¼ 351.80, P < 0.0001) and tomato maturity (F ¼ 96.13, P < 0.0001) were highly significant. The effects of tomato maturity on Salmonella growth inside tomatoes are consistent with the reports that red tomatoes were significantly more conducive to proliferation of Salmonella than green tomatoes (Shi et al, 2007; and that the gene expression in Salmonella changes in response to specific metabolites present within immature tomato fruit Noel et al, 2010). Statistically significant two-way and three-way interactions were as follows: potassium fertilization levels  harvest time (F ¼ 2.38, P ¼ 0.027), Salmonella strain  harvest time (F ¼ 9.03, P < 0.0001), tomato maturity  harvest time (F ¼ 10.41, P < 0.0001), nitrogen fertilization levels  potassium fertilization levels  harvest time (F ¼ 1.84, P ¼ 0.037), tomato cultivar  nitrogen fertilization level  harvest time (F ¼ 2.50, P ¼ 0.021), tomato maturity  nitrogen fertilization levels  harvest time (F ¼ 2.10, P ¼ 0.014), and tomato maturity  tomato cultivar  harvest time (F ¼ 4.33, P ¼ 0.0002), respectively (for the results of all F-tests, see Table 1).…”
Section: Resultssupporting
confidence: 88%
“…The main effects of the tomato cultivar (F ¼ 0.62, P ¼ 0.432) and Salmonella strain (F ¼ 0.60, P ¼ 0.4386) were not significant, while the main effects of the harvest time (F ¼ 351.80, P < 0.0001) and tomato maturity (F ¼ 96.13, P < 0.0001) were highly significant. The effects of tomato maturity on Salmonella growth inside tomatoes are consistent with the reports that red tomatoes were significantly more conducive to proliferation of Salmonella than green tomatoes (Shi et al, 2007; and that the gene expression in Salmonella changes in response to specific metabolites present within immature tomato fruit Noel et al, 2010). Statistically significant two-way and three-way interactions were as follows: potassium fertilization levels  harvest time (F ¼ 2.38, P ¼ 0.027), Salmonella strain  harvest time (F ¼ 9.03, P < 0.0001), tomato maturity  harvest time (F ¼ 10.41, P < 0.0001), nitrogen fertilization levels  potassium fertilization levels  harvest time (F ¼ 1.84, P ¼ 0.037), tomato cultivar  nitrogen fertilization level  harvest time (F ¼ 2.50, P ¼ 0.021), tomato maturity  nitrogen fertilization levels  harvest time (F ¼ 2.10, P ¼ 0.014), and tomato maturity  tomato cultivar  harvest time (F ¼ 4.33, P ¼ 0.0002), respectively (for the results of all F-tests, see Table 1).…”
Section: Resultssupporting
confidence: 88%
“…The capacity of S. enterica (and other enteric pathogens) to readily multiply within plant tissues led to the hypothesis that persistence on plants is a part of the Salmonella life cycle, serving as reservoirs prior to reinfection of the preferred animal hosts (2)(3)(4)(5). Several studies have dissected the molecular basis of plant-Salmonella interactions (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the entire complement of genetic functions required for plant colonization by Salmonella is not yet known.…”
mentioning
confidence: 99%
“…It involves major changes in the bacterial transcriptome and requires genes involved in amino acid biosynthesis and transport, cellulose production, fimbriae, regulators, and surface structures (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of the same mechanisms were involved in the colonization of both vegetative and reproductive tissues on different plant species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On tomato, S. enterica has been reported to move systemically reaching fruits and seeds from leaves (Gu et al 2011). Once within the fruits, the pathogen can multiply to high densities (Gu et al 2011;Noel et al 2010). A recent study demonstrated that Escherichia coli can internally colonize both leaves and roots of lettuce and spinach (Wright et al 2013).…”
Section: Bacteriamentioning
confidence: 99%